Smile pricing explained - Austing, Peter; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Smile Pricing Explained provides a clear and thorough explanation of the concepts of smile modelling that are at the forefront of modern derivatives pricing. The key models used in practice are covered, together with numerical techniques and calibration.
Keywords: Derivative securities; Interest rates; Banks and banking